Feedback Linearization Control Design for Battery/SMES Hybrid Energy Storage Systems Used in Distribution Network - Tang, Chengye; Huang, Yonghong (Frontiers in Energy Research, 2021)
A battery/superconducting magnetic energy storage (SMES) hybrid energy storage system (BSM-HESS) is designed for a power system. Meanwhile, a nonlinear feedback control (FLC) is adopted to achieve smooth and fast-tracking performance, and a rule-based strategy (RBS) is applied for power demand allocation. FLC can effectively compensate for the system’s nonlinearity to obtain the global consistent control performance; thus, it can properly solve the nonlinearity and modeling uncertainty of BSM-HESS. The effectiveness and advantages of FLC are evaluated via three cases, namely, heavy load condition, light load condition, and robustness with uncertain BSM-HESS parameters. Simulation results show that compared with proportional–integral–derivative (PID) control, FLC can achieve the best dynamic performance under various working conditions, which is beneficial for the system to quickly restore stable operation after large disturbance. In addition, the control cost of FLC is lower than that of PID control under both heavy load and light load conditions.